Effect evaluation of a road safety education program based on victim testimonials in high schools in Belgium. (September 2016) - Cuenen, Ariane; Brijs, Kris; Brijs, Tom; Van Vlierden, Karin; Daniels, Stijn; Wets, Geert
Highlights: The study investigated the effects of an education program for high school students using testimonials of traffic victims. The program positively affected socio-cognitive and behavioral variables among students of general and occupational education, albeit the effects were small. Two months after program attendance, small-to-medium sized positive effects on the majority of the socio-cognitive and behavioral variables were found for male and female students. Participants were affected both cognitively and emotionally, with differences in terms of gender and education type. The impact of the program on participants' cognitive and emotional estate is relevant for determining the program's effect on socio-cognitive and behavioral variables. Abstract: For several decades policy makers worldwide have experimented with testimonials as a strategy to promote road safety supportive views in a wide variety of target populations such as recidivists and students. In its basic format, a (relative of) a victim or an offender brings a personal testimonial of what it is to experience a traffic accident. The underlying idea is that such a testimonial will emotionally affect participants, thereby stimulating them to cognitively reflect upon their own behavior and responsibility as a road user. Unfortunately, empirical literature on the effectiveness of this strategy is rather scarce and inconsistent. This study investigated the effect of a large-scale program with victim testimonials for high schools in Belgium on five socio-cognitive and behavioral variables drawn from the Theory of Planned Behavior (i.e., attitude, subjective norm, perceived behavioral control, behavioral intention and behavior). Moreover, this study investigated program effects on participants' cognitive and emotional estate and whether this influences the program's impact on socio-cognitive and behavioral variables. Our test sample included 1362 students, who were assigned to a baseline – follow-up group and a post-test – follow-up group. We questioned both groups, a first time (just before or after session attendance) on paper, and a second time (two months after session attendance) online. Results indicate the program had, both immediate and two months after attendance, small to medium positive effects on most socio-cognitive and behavioral variables. However, effects depended on participants' demographic profile, their baseline values on the socio-cognitive and behavioral variables, and the degree to which they were cognitively/emotionally affected by the program. We discuss the practical implications of these findings and formulate recommendations for the development of future interventions based on victim testimonials.